2020
DOI: 10.3390/biom10050719
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Open Chromatin Methylome Profiles in Colorectal Cancer

Abstract: The methylome of open chromatins was investigated in colorectal cancer (CRC) to explore cancer-specific methylation and potential biomarkers. Epigenome-wide methylome of open chromatins was studied in colorectal cancer tissues using the Infinium DNA MethylationEPIC assay. Differentially methylated regions were identified using the ChAMP Bioconductor. Our stringent analysis led to the discovery of 2187 significant differentially methylated open chromatins in CRCs. More hypomethylated probes were observed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A few studies have shown the dysregulation of DNA methylation in colon cancer including EYA4 , which was hypermethylated and treatment with demethylating agents caused induction of its expression [ 46 ]. In agreement with Kim et al [ 31 ] and Moon et al [ 47 ], we have restored the expression of EYA4 after treating the Caco-2 and LoVo colon cancer cells with 1 μ M 5-Aza-CdR for 72 hours, this implies the possible mechanism of involvement of DNA methylation in hampering the expression of EYA4 [ 31 ], which could accelerate colon cancer formation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown the dysregulation of DNA methylation in colon cancer including EYA4 , which was hypermethylated and treatment with demethylating agents caused induction of its expression [ 46 ]. In agreement with Kim et al [ 31 ] and Moon et al [ 47 ], we have restored the expression of EYA4 after treating the Caco-2 and LoVo colon cancer cells with 1 μ M 5-Aza-CdR for 72 hours, this implies the possible mechanism of involvement of DNA methylation in hampering the expression of EYA4 [ 31 ], which could accelerate colon cancer formation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four studies were found; of them, only those using Infinium Human Methylation 450K and EPIC BeadChips and providing adequate raw and clinical data were selected for further analysis. Four studies, namely GSE99788 [ 38 ], GSE149282 [ 39 ], GSE122126 [ 40 ] and GSE105798 [ 41 ], were recruited for our analysis. The description of study groups and correlations is presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Human 5-oxoprolinase, OPLAH, was shown to be hypermethylated in our study, which had a significant impact on the gene’s downregulation, suggesting a possible contribution to CRC through the dysregulation of gene expression. Numerous investigations have also revealed that OPLAH is frequently hypermethylated in CRC versus normal tissues [ 40 , 60 ]. Despite a paucity of information on OPLAH methylation in cancer, several patents have been filed for its applicability in cancer detection.…”
Section: Discussionmentioning
confidence: 99%